Nik-related kinase regulates trophoblast proliferation and placental development by modulating AKT phosphorylation. - Yuka Morioka; Jin-Min Nam; Takashi Ohashi (PLoS ONE)
Nik-related kinase (Nrk) is a Ser/Thr kinase and was initially discovered as a molecule that was predominantly detected in skeletal muscles during development. A recent study using Nrk-null mice suggested the importance of Nrk in proper placental development; however, the molecular mechanism remains unknown. In this study, we demonstrated that differentiated trophoblasts from murine embryonic stem cells (ESCs) endogenously expressed Nrk and that Nrk disruption led to the enhanced proliferation of differentiated trophoblasts. This phenomenon may reflect the overproliferation of trophoblasts that has been reported in enlarged placentas of Nrk-null mice. Furthermore, we demonstrated that AKT phosphorylation at Ser473 was upregulated in Nrk-null trophoblasts and that inhibition of AKT phosphorylation cancelled the enhanced proliferation observed in differentiated Nrk-null trophoblasts. These results indicated that the upregulation of AKT phosphorylation was the possible cause of enhanced proliferation observed in Nrk-null trophoblasts. The upregulation of AKT phosphorylation was also confirmed in enlarged Nrk-null placentas in vivo, suggesting that proper regulation of AKT by Nrk was important for normal placental development. In addition, our detailed analysis on phosphorylation status of AKT isoforms in newly established trophoblast stem cells (TSCs) revealed that different levels of upregulation of AKT phosphorylation were occurred in Nrk-null TSCs depending on AKT isoforms. These results further support the importance of Nrk in proper development of trophoblast lineage cells and indicate the possible application of TSCs for the analysis of differently regulated activation mechanisms of AKT isoforms.